Perceived Value as a Mediator of Service Experience, Atmosphere, and Customer Engagement on Customer Satisfaction: Evidence From Fitness Center Customers in Lamongan - Nawari; Muhammad Hafidh Nashrullah; Siti Shoimah (Global Research Collaboration, 2026)
Indonesia’s expanding fitness industry has intensified competition, making customer satisfaction crucial for retention and sustainability. However, limited research explains how Service Experience, Atmosphere, and Customer Engagement influence satisfaction through Perceived Value in local fitness-center contexts. This study aims to analyze the effects of Service Experience, Atmosphere, and Customer Engagement on Customer Satisfaction, with Perceived Value as a mediating variable among fitness-center members in Lamongan. A quantitative explanatory design was applied using a cross-sectional survey. Structured questionnaires were distributed to 220 active members, and the proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings show that Service Experience, Atmosphere, and Customer Engagement positively and significantly affect Perceived Value. Customer Engagement and Perceived Value positively and significantly affect Customer Satisfaction. Atmosphere has no significant direct effect, while Service Experience has a significant negative direct effect on Customer Satisfaction. Perceived Value mediates the effects of all three antecedents on Customer Satisfaction. The study concludes that Perceived Value is a central mechanism linking service-related experiences to satisfaction and supporting stronger customer loyalty, competitiveness, and long-term relationships in Indonesia’s increasingly competitive local fitness service market today.